2021
DOI: 10.1111/gcb.15945
|View full text |Cite
|
Sign up to set email alerts
|

Climate warming promotes deterministic assembly of arbuscular mycorrhizal fungal communities

Abstract: Arbuscular mycorrhizal fungi (AMF) significantly contribute to plant resource acquisition and play important roles in mediating plant interactions and soil carbon (C) dynamics. However, it remains unclear how AMF communities respond to climate change.We assessed impacts of warming and precipitation alterations (30% increase or decrease) on soil AMF communities, and examined major ecological processes shaping the AMF community assemblage in a Tibetan alpine meadow. Our results showed that warming significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 107 publications
(144 reference statements)
7
12
0
Order By: Relevance
“…Our analyses indicate that warming leads to changes in allocation, consistent with other observations and experimental evidence 22,23 . Liu et al 23 , for example, have shown that warming leads to a shift towards deeper rooting and more below-ground carbon allocation in alpine grasslands, allowing plants to acquire more water and nutrients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our analyses indicate that warming leads to changes in allocation, consistent with other observations and experimental evidence 22,23 . Liu et al 23 , for example, have shown that warming leads to a shift towards deeper rooting and more below-ground carbon allocation in alpine grasslands, allowing plants to acquire more water and nutrients.…”
Section: Discussionsupporting
confidence: 92%
“…Increased VPD and warming had negative effects in both areas, but when compared with other environmental factors, the impact of VPD and warming was greater in energy limited areas (−0.106±0.043% yr −1 , −0.132±0.031% yr −1 respectively) than water limited areas (−0.142±0.064% yr −1 , −0.078±0.026% yr −1 respectively). This difference in response reflects the fact that increased atmospheric aridity and warming in energy limited areas necessitates increased below-ground allocation for nutrient and water uptake 22,23 and is consistent with an inferred increase in the unit cost of constructing and maintaining leaves (zcost) (Supplementary Fig. 8).…”
Section: Resultssupporting
confidence: 63%
“…To download the taxonomic compositions of soil microbes that conduct broad and narrow functions, in the "Analysis" function of the MG-RAST server (https://www.mg-rast.org/mgmain. html?mgpage=analysis, last access: 10 September 2019), we loaded SEED subsystems (levels 3, 2, and 1) as functional profiles and RefSeq (Tatusova et al, 2013) databases (genus, family, order, class, and phylum levels) as taxonomic compositions (Xu et al, 2021) for each soil metagenome. The detailed protocols of the MG-RAST server were followed to analyze the metagenomic functions (Meyer et al, 2008;Wilke et al, 2017).…”
Section: Data Collectionmentioning
confidence: 99%
“…Nowadays, metagenomics is increasingly being used as a promising comparative tool (Tringe et al, 2005) to study the relationship between functional and taxonomic diversities (Fierer et al, 2012(Fierer et al, , 2013Souza et al, 2015;Pan et al, 2014;Leff et al, 2015). The growing wealth of soil metagenome data is thus well poised to aid in the generalization of global patterns of microbial attributes and the standardization of frameworks for the consistent representation of microbial communities (Xu et al, 2021). However, a synthetic metagenomic analysis to assess how general microbial taxonomic and functional beta diversities differ between broad and narrow functions across the globe is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The Mantel test indicated no strong correlation between the fungal community structure and soil factors. The results of an alpine meadows study showed that 3 years of warming enhances the deterministic processes of the fungal community (Xu et al, 2022 ). Unexpectedly, a decrease in the relative importance of random processes of the fungal communities was observed after one growing season of warming in our study, indicating that the fungal communities in alpine peatlands are highly sensitive to temperature change.…”
Section: Discussionmentioning
confidence: 99%